Nonparametric methods for the characteristic model - Laura Blow; Martin James Browning; Ian A. Crawford (Centre for Microdata Methods and Practice (cemmap), 2004)
Characteristics models have been found to be useful in many areas of economics. However, their empirical implementation tends to rely heavily on functional form assumptions. In this paper we develop a revealed preference-based nonparametric approach to characteristics models. We derive the minimal necessary and sufficient empirical conditions under which data on the market behaviour of individual, heterogeneous, pricetaking consumers are nonparametrically consistent with the consumer characteristics model. Where these conditions hold, we show how information may be recovered on individual consumer's marginal valuations of product attributes. In some cases marginal valuations are point identi- fied and in other cases we can only recover bounds. Where the conditions fail we highlight the role which the introduction of unobserved product attributes can play in rationalising the data. We implement these ideas using consumer panel data on the Danish milk market.
Keywords: C43; D11; 330; Product characteristics; revealed preference; Nichtparametrisches Verfahren; Offenbarte Präferenzen; Milchmarkt; Dänemark; Statistische Verteilung